Assessment of educational resources for effective teaching and learning in public senior secondary schools in Port Harcourt Metropolis, Rivers State - Ndimele, Stanley Chimezie; Sam-Kalagbor, Victoria Osaruchi (Faculty of Natural and Applied Sciences Journal of Mathematics, and Science Education, 2023)
This study assessed educational resources for improved teaching and learning in government-owned senior secondary schools in Port Harcourt Metropolis, Rivers State. A descriptive survey design was adopted. The population of the study was 55,188 (1,899 teachers and 53,289 students) in all the 39 public senior secondary schools in Rivers Port Harcourt Metropolis, Rivers State (Rivers State Senior Secondary Schools Board, Port Harcourt, 2022). The sample was 400 respondents (120 teachers and 280 students). A simple random sampling technique was used for sample selection. Assessment of Educational Resources Questionnaire developed by the researchers was used for data collection. An expert in measurement and evaluation and a public-school principal in Port Harcourt Metropolis determined the face and content validity. The Cronbach Alpha method was used to establish reliability coefficients of 0.74, 0.70 and 0.72 for the three clusters of the questionnaire. Research questions were answered with mean, frequency count, and percentage, while hypotheses were tested with Independent sample t-test at a 0.05 level of significance. Results showed that educational material resources are available to a high extent for teaching and learning, and that a greater percentage of teachers in government-owned senior secondary schools in Port Harcourt Metropolis are not qualified for teaching based on teaching qualifications. It was recommended, among others, that teachers without teaching qualifications should be encouraged to attend in-service teacher education programs to obtain the requisite qualifications for teaching.